A difference-of-convex functions approach for sparse PDE optimal control problems with nonconvex costs - Merino, Pedro (Computational optimization and applications, 2019)
We propose a local regularization of elliptic optimal control problems which involves the nonconvex L q quasi-norm penalization in the cost function. The proposed Huber type regularization allows us to formulate the PDE constrained optimization instance as a DC programming problem (difference of convex functions) that is useful to obtain necessary optimality conditions and tackle its numerical solution by applying the well known DC algorithm used in nonconvex optimization problems. By this procedure we approximate the original problem in terms of a consistent family of parameterized nonsmooth problems for which there are efficient numerical methods available. Finally, we present numerical experiments to illustrate our theory with different configurations associated to the parameters of the problem.